Respuesta :

Answer:

OPTION C: y = -2y² - 8y - 8

                    x = y + 2

Step-by-step explanation:

The given equations are:

[tex]$ y = -2x^2 \hspace{20mm} \hdots (1) $[/tex]

[tex]$ y = x - 2 \hspace{20mm} \hdots (2) $[/tex]

From Equation (2), we get:

x = y + 2

Substituting this value of x in Equation (1), we get:

y = -2(y + 2)²

Expanding it in [tex]$ (a + b)^2  = a^2 + 2ab + b^2 $[/tex], we get:

y = -2{y² + 4y + 4}

y = - 2y² - 8y - 8

Therefore, OPTION C is the answer.

Answer: C on edge 2022

Step-by-step explanation:

if wrong i’m gay and Bidens a good president *they almost all suck anyways*

ACCESS MORE